2016
DOI: 10.1021/jacs.6b10225
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Driven Cooperative Spin-Crossover, Large-Volume Collapse, and Semiconductor-to-Metal Transition in Manganese(II) Honeycomb Lattices

Abstract: Spin-crossover (SCO) is generally regarded as a spectacular molecular magnetism in 3d-3d metal complexes and holds great promise for various applications such as memory, displays, and sensors. In particular, SCO materials can be multifunctional when a classical light- or temperature-induced SCO occurs along with other cooperative structural and/or electrical transport alterations. However, such a cooperative SCO has rarely been observed in condensed matter under hydrostatic pressure (an alternative external st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 50 publications
(86 reference statements)
5
74
4
Order By: Relevance
“…Note that the previous experimental study suggested the formation of Mn zigzag chains in the high-P phase [22], in contrast to our DFT+U and eDMFT results.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Note that the previous experimental study suggested the formation of Mn zigzag chains in the high-P phase [22], in contrast to our DFT+U and eDMFT results.…”
contrasting
confidence: 99%
“…1(a) in the main text, the value of critical pressure predicted by DFT+U calculations is twice bigger than the one reported in Ref. 22 (63 vs. 30 GPa). For a better understanding of this discrepancy, we perform calculations with interpolating structures between the honeycomb high-spin and the dimerized low-spin structures as shown in Fig.…”
Section: Comparison With Dft+u and Dmft In Mnps3contrasting
confidence: 54%
See 2 more Smart Citations
“…In the pursuit of abrupt pressure-driven SCOs in TM chalcogenides, we became aware of the essential role of the TM-sublattice dimensions in the cooperativeness of SCO 26 , 27 . We have discovered abrupt pressure-driven phase transitions accompanied by a high-to-low spin-state transition of Mn 2+ in the transition from three-dimensional (3D) NaCl-type Mn X to two-dimensional (2D) MnP X 3 ( X = S, Se) with an Mn 2+ honeycomb lattice.…”
Section: Introductionmentioning
confidence: 99%